Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kedisiplinan Pegawai (Divisi Pengujian Kendaraan Bermotor Dinas Perhubungan Kabupaten Ciamis) - Rizky Hardi Pratama; Mila Karmila; Suci Putri Lestari (Global Leadership Organizational Research in Management, 2023)
The purpose of this research was to determine the effect of compensation and work motivation on employee discipline in the Motorized Vehicle Testing Division of the Ciamis Regency Transportation Service. This research is a quantitative research. The population in this research were employees of the Motor Vehicle Testing Section of the Ciamis Regency Transportation Service. Sampling in this research used a saturated sample of 43 respondents. The analytical method used in this research was multiple linear regression analysis with the help of SPSS 25 software. The results showed that compensation and work motivation simultaneously had an effect on employee discipline. Partially, compensation variables affect employee discipline. Partially, work motivation variables affect employee discipline